If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + 11 = 3p Reorder the terms: 11 + p = 3p Solving 11 + p = 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 11 + p + -3p = 3p + -3p Combine like terms: p + -3p = -2p 11 + -2p = 3p + -3p Combine like terms: 3p + -3p = 0 11 + -2p = 0 Add '-11' to each side of the equation. 11 + -11 + -2p = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -2p = 0 + -11 -2p = 0 + -11 Combine like terms: 0 + -11 = -11 -2p = -11 Divide each side by '-2'. p = 5.5 Simplifying p = 5.5
| (1/2)/(7/12)=x | | 6(x-90)=3x+2 | | .05(x)=20 | | -2.1=-0.6u+0.3u | | -2.1=-0.6+0.3 | | (6x-1)+121=180 | | s-2/3=2 | | 12y^2-6y=0 | | 3/2t=-1/3 | | n*2+5=-n-13 | | (3x+9)+132=180 | | -2g-3(7g+6)=-156 | | 1k+9=6k-66 | | g(x)=-2x+13 | | 2=4/w | | -3(3b-2)= | | -5/5i | | 4/5y-20=160 | | 22x=23x-1 | | 8X=7X-21 | | 5-11=-3z | | 7(5x-4)-(5+7x)= | | 4r-p=q | | 12g=24 | | 9(6-5x)-2(3+6x)= | | 5(3x-2)=(2x-1) | | g(x)=3-9x | | 9(8+5m)= | | -8v+3(v+3)=14 | | 4(9x+8)-9(6-3x)= | | (x+4)(x+2)-3=0 | | (8x-4)+92=180 |